AN ANALYSIS ON AFFIXES USED IN JOE BIDEN’S SPEECH - Salsabillah Nurulhaq Baderan; Ignatius J. C Tuerah; Sanerita T. Olii (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This study focuses on identifying the most common types of affixes that younger people learning new words encounter. Its purpose is to assist students at this level in better understanding the words they come across. It has been determined that only a relatively small number of prefixes and suffixes are worth teaching in intermediate-level courses. The research process involved gathering data from library databases and online journals to decide on the research objectives, research objects, data sources, data collection methods, and data analysis. The main emphasis of this study is on suffix affixes directly extracted from Joe Biden's speech, with included data extracts to enhance the research findings. The analysis of the speech revealed that the prefix "re-" and the suffixes "-ed" and "-ing" are more prominent than other prefixes and suffixes. Based on these findings, the researcher suggests that future studies should explore affixes in EFL textbooks and the teaching of affixes in schools. It is important for teachers to not only teach English words but also explain how those words are formed in order to enhance students' English proficiency.